Myanmar Government's International Crimes Against the Rohingya and The Enforcement Under the 1998 Rome Statute - Ilham Adepio, M. (Universitas Negeri Semarang, 2025)
This article explores the international crimes committed by the Myanmar government against the Rohingya in Rakhine State under the 1998 Rome Statute and evaluates possible avenues for accountability through the International Criminal Court (ICC) or universal Jurisdiction. Utilising a normative-legal framework and a descriptive-analytical approach, a systematic review of relevant treaties and case law is conducted to categorise Myanmar’s orchestrated violence, discrimination, and mass killings. The evidence indicates that these violations meet the criteria for both genocide and crimes against humanity, given their organised, systemic nature, which is aimed at eradicating the Rohingya population. The ICC’s authority to enforce compliance, as outlined in Article 13 (b) of the Rome Statute, is contingent upon a referral from the United Nations Security Council under Chapter VII of the UN Charter. This process bears a resemblance to the 2011 Libyan referral against Muammar Gaddafi. However, the absence of ratification by Myanmar and the prevailing geopolitical deadlock within the Security Council serve to impede this course of action. As an alternative, universal jurisdiction provides a practical mechanism, as exemplified by Belgium’s prosecution related to the Sabra-Shatila massacre, allowing states to try atrocity crimes irrespective of location or nationality. The study emphasises the necessity of international political resolve and cross-border judicial cooperation, advocating for a coordinated multilateral strategy to address existing accountability gaps and advance justice for the Rohingya.